Load distribution after unilateral condylar fracture with shortening of the ramus: a finite element model study - Loreine M. L. Helmer; Cornelis Klop; Frank Lobbezoo; Jan de Lange; Jan Harm Koolstra; Leander Dubois (Head & Face Medicine, 2023)
Abstract Objectives After a fracture of the condyle, the fractured ramus is often shortened, which causes premature dental contact on the fractured side and a contralateral open bite. The imbalance could change the load in the temporomandibular joints (TMJs). This change could lead to remodelling of the TMJs to compensate for the imbalance in the masticatory system. The load in the non-fractured condyle is expected to increase, and the load in the fractured condyle to decrease. Materials and methods These changes cannot be measured in a clinical situation. Therefore a finite element model (FEM) of the masticatory system was used. In the FEM a fractured right condyle with shortening of the ramus was induced, which varied from 2 to 16 mm. Results Results show that, with a larger shortening of the ramus, the load in the fractured condyle decreases and the load in the non-fractured condyle increases. In the fractured condyle during closed mouth a major descent in load, hence a cut-off point, was visible between a shortening of 6 mm and 8 mm. Conclusions In conclusion, the change of load could be associated with remodelling on both condyles due to shortening of the ramus. Clinical relevance The cut-off point implies that shortening over 6 mm could present more difficulty for the body to compensate.